Optimal and acceptable reliabilities for structural design. (January 2019) - Fischer, Katharina; Viljoen, Celeste; Köhler, Jochen; Faber, Michael H.
Highlights: A generic framework for structural design optimization is presented. The framework is combined with a life safety acceptance criterion. Optimal and acceptable reliabilities for structural design are derived. The application for component and system level design is discussed. A clear relation to structural robustness is established. Abstract: A common approach to define criteria to reliability performance of structures in the development of semi-probabilistic design codes and for probabilistic design of individual structures is to make use of the tentative target reliabilities provided in the JCSS Probabilistic Model Code. An acceptable level of life safety is, however, not guaranteed when applying the target reliabilities provided by the JCSS, as these have been derived based on monetary optimization. In the present paper, the underlying generic framework for structural design optimization is reviewed and extended for the derivation of life safety related target reliabilities based on the marginal lifesaving costs principle. The resulting minimum acceptable reliabilities may be used in combination with the JCSS target reliabilities to achieve designs that are both cost-efficient and consistent with societal preferences for lifesaving investments. The framework presented in this paper forms the basis for the target reliabilities defined in ISO 2394:2015, where the target reliabilities proposed by the JCSS have been combined with minimum acceptable reliabilities to ensure societal acceptability in terms of life safety. An extended discussion of the general framework and its underlying assumptions includes considerations about the application of the target reliabilities at component or system level, accounting for structural robustness, as well as implications for the interpretation of the main variables entering the framework.